Improved Modeling of Bulk Acoustic Wave Resonators and Filters - Hagelauer, Amelie Marietta; Link, Andreas; Bader, Bernhard; Marksteiner, Stefan; Wagner, Karl Christian; Weigel, Robert (IEEE International Ultrasonics Symposium 2010, 2010)
Duplexers and filters for mobile radio are one of the classic field of application for the BAW technology. In recent years the size of the devices has been reduced by about a half and the trend is still toward more compact designs with higher performance at the same time. This translates directly to very demanding requirements on the effective coupling coefficient and on the quality factors of the underlying BAW resonators. Measurements show that the size and the shape of the resonators have a significant influence on the overall performance. Hence, size-relevant effects need to be considered in ID-simulation, which is the base for fast filter optimization. To evaluate the influence of the resonator size on the filter performance we analyzed several SMR-BAW resonator area and shape variations in combination with different overlap sizes in a series of experiments. Moreover, the influence of the overlap size on different resonator areas is studied with 2D-FEM simulations. In this paper we present the results of our resonator measurements. The results are basis for developing a modified ID model for designing BAW filters. Additionally, a new method for the extraction of an 'equivalent acoustic impedance' for the description of the acoustics is presented and compared to the modified ID-model.
elib2cris::1512001600,hagelauer2010
Keywords: acoustic resonator filters; bulk acoustic wave devices; finite element analysis; 2D-FEM simulations; BAW filters; BAW technology; ID-simulation; SMR-BAW resonator; bulk acoustic wave resonators; effective coupling coefficient; equivalent acoustic impedance extraction; fast filter optimization; resonator measurements; resonator shape; resonator size; q-factor